Arbitration and Other Alternative Dispute Resolution for Commercial Dispute (Reviewed from the Strengths of ADR and Decision of Arbitration) - Suherman, Suherman (Brawijaya Law Journal, 2019)
Arbitration and other alternative dispute resolution (ADR) can be used as an option for parties who conduct commercial transactions. This research is crucial to analyse what is the best dispute method Â for parties to be able to resolve their commercial business disputes. It is argued that the most important of ADR is the efficiency and effectivines in relation to the enforcement of a judgement on the commercial dispute especially foreign arbitral award.This research also seeks to analyse strengths and weaknesses of each ADR method because it is very important to know in resolving disputes in the field of trade and also related to the implementation of decisions, especially in foreign arbitral award and how to improve decisions and applied in Indonesia in relation to commercial dispute. The research method used in this research is normative juridical consisting of primary, secondary and tertiary legal materials, which were collected by conducting a literature review and interview technique and then processed qualitatively according to the problems and the theoretical framework logically and systematically to achieve the objective of this research, namely finding the best alternative dispute resolution in commercial dispute resolution in business transactions.This paper argued that while each of ADR method has their own strengths and weaknesses, business actors mostly prefer too have arbitration method as their ADR method in solving their disputes. However,the applying mechanism of foreign arbitration awards need further attention from Indonesian government.